Risk factors of chronic low back pain among Syrian patients: across- sectional study - Fater A. Khadour; Younes A. Khadour; Weaam Alhatem; Deema Albarroush; Abdullah. Z. Halwani; Micheal M. Goirge; Xiuli Dao (BMC Neurology)
Abstract Background Chronic low back pain is a global health issue that leads to disability and significant economic costs. However, it has received limited attention in low- and middle-income countries. This study aimed to determine the prevalence of chronic low back pain and identify its associated risk factors among the Syrian population. Method This cross-sectional study included adults aged 18 years and above who visited neurology outpatient clinics in seven centers across four provinces (Damascus, Aleppo, Homs, and Latakia) between November 2021 and January 2022. A self-administered questionnaire was utilized to collect data on socio-demographic factors, work-related characteristics, and information about chronic low back pain. Descriptive statistics were employed to summarize the demographic characteristics of the participants. Multivariate logistic regression analysis was conducted to assess the risk factors for chronic low back pain. Results A total of 830 adults participated in the study. The overall prevalence of chronic low back pain was estimated to be 16.7% (95% CI: 13.6–25.5), with females having a higher prevalence 17.8%, (95% CI: 14.8–27.5) compared to males 15.4%, (95% CI: 14.8–23.1). Multivariate regression analysis revealed several risk factors associated with chronic low back pain. These included being overweight (aOR: 5.2, 95% CI: 1.9–8.4, p = 0.041), having no formal education (aOR: 4.6, 95% CI: 1.6–8.4, p = 0.001), lack of regular physical exercise (aOR: 3.7, 95% CI: 1.8–6.3, p = 0.003), smoking more than 11 cigarettes per day (aOR: 4.8, 95% CI: 2.4–12.6, p = 0.003), leading a sedentary lifestyle (aOR: 8.3, 95% CI: 3.5–18.9, p = 0.002), manual work (aOR: 7.9, 95% CI: 5.9–16.7, p = 0.003), and adopting a stooped sitting posture (aOR: 3.5, 95% CI: 0.9–8.2, p = 0.039). Conclusion This study demonstrates that the prevalence of chronic low back pain in Syria is higher compared to other regions, and it is associated with several risk factors. These risk factors include a lack of formal education, being overweight, insufficient regular physical exercise, smoking, leading a sedentary lifestyle, manual work, and adopting a stooped sitting posture. These findings underscore the importance of addressing these modifiable risk factors to prevent and manage chronic low back pain in the Syrian population.